A multi-faceted structural, thermodynamic, and spectroscopic approach for investigating ethanol dehydration over transition phase aluminas. Issue 1 (9th December 2022) - Strange, Nicholas A.; Adak, Sourav; Stroupe, Zachary; Crain, Christopher A.; Novak, Eric C.; Daemen, Luke L.; Larese, J. Z.
Abstract : The surface-catalyzed dehydration of ethanol over transition phase aluminas was studied using a multi-faceted structural and thermodynamic characterization approach, which enabled a detailed examination of the reaction mechanism using INS. Abstract : Understanding the role that the surface of a material plays in the mediation of a chemical reaction at the atomic level is paramount to the optimization and improvement of catalytic materials. While this area of research has matured over several decades, few techniques are sensitive enough to directly examine and differentiate the behavior of molecular adsorbates during the course of the chemical reaction with a substrate. In this study, a combined approach which involves structural characterization techniques, volumetric adsorption, temperature programmed desorption, and inelastic neutron scattering (INS) was used to investigate the mechanism of ethanol dehydration on the surface of transition phase aluminas. The alumina samples employed were extensively characterized using X-ray diffraction, solid-state 27 Al nuclear magnetic resonance spectroscopy, and thermogravimetric analysis with differential scanning calorimetry. A high-precision volumetric adsorption apparatus was used to characterize the surface area and to controllably dose ethanol onto the surface of the aluminas. A modified temperature programmed desorption (TPD) method which samples the molecular composition of the vapor at discrete temperatures in a closed cell is described. INS results were used to confirm adsorption of ethanol on γ- and θ-alumina and show the reaction of ethanol and subsequent formation of ethylene as a function of temperature. The TPD and INS results affirm that the dehydration reaction and subsequent formation of ethylene on both γ- and θ-aluminas occur rapidly at 300 °C, though ethanol is still observed on θ-alumina indicating fewer active sites. These results demonstrate the value of a multi-faceted characterization approach, featuring INS, towards providing a detailed understanding of the ethanol dehydration mechanism on θ-alumina and further provide the basis for extending this approach to other systems in heterogeneous catalysis and areas where molecule-substrate interactions are poorly understood.